The development economist as historian of economics: The case of William J. Barber - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2018)
The paper shows how William Barber's background as a development economist influenced his research agenda in the history of economic thought, in terms of the questions he asked and the way he approached them. The links between the history of economic theory and of policy-making are highlighted, as well as Barber's investigation of the engagement of British economists with India's economic matters throughout the time span of the English East India Company.
Keywords: B12; B30; 330; William J. Barber; development economics; history of economics; policy-making; classical economics